Transparência eletrônica dos tribunais de contas conforme a Lei de Responsabilidade Fiscal (LRF) e a Lei de Acesso á Informação (LAI) - Reis, Alexandre Rosa (2018)
Corporate governance also applies to the Public Sector. Among the principles of governance are disclosure and accountability. The first concerns aspects of disclosure and transparency, and the second, accountability. The courts of auditors act as external control bodies for the Public Administration, in support of social control as well, therefore, the courts act to optimize governance and public management. The Fiscal Responsibility Law (LRF) and the Access to Information Law (LAI) focused on public transparency and accountability, in their electronic aspect. Thus, the general objective of the work was to verify the degree of electronic transparency of the Brazilian Courts of Accounts, according to the provisions of the LRF and LAI. Therefore, this study was descriptive, qualitative and quantitative and documentary. The 32 courts of accounts of the states and municipalities in operation in Brazil were examined. To assess the degree of transparency, the adapted model by Nunes (2013) was used, whose notes could be included in the closed interval [-50; +150]. The results showed that the national average was only 6.64 (very low degree of electronic transparency). The five courts of accounts with the best results showed only a moderate degree of electronic transparency. They were: TCM / PA, TCE / ES, TCE / PI, TCE / PB and, TCE / MT. The five courts with the worst results had a very low degree of transparency. They were: TCE / SE, TCE / AM, TCE / MS, TCE / AL and TC / DF. In the ranking of the regions, the South Region had an average of 11.97 (low degree of electronic transparency) and the other regions all had a 'very low' degree of transparency, with emphasis on the Midwest region, with the lowest average - 0.10. In summary, the results indicated that there is still a long way to go for the managers of the courts of auditors to achieve at least moderate degrees of electronic transparency, however, the first steps towards meeting electronic transparency, along the lines imposed by the LRF and by LAI have already been given.